Application of lignosulfonate and starch as a somponent of rubber blends - Hudec; Alexy P; Feranc J; Kubackova J; Preto J; Slovakia (Kautschuk Gummi Kunststoffe, 2013)
The effect of a multicomponent filler composed of calcium lignosulfonate, cornstarch and silica on the morphology, vulcanization characteristics, mechanical and dynamical-mechanical properties of rubber blends and vulcanizates was examined. The measured properties were evaluated as a function of three selected factors by applying the design of experiment (DOE) mrthod. The scorch time of rubber compounds was found to be affected by the total volume filling and lignosufonate content. An increase in the lignosulfonate content caused a decrease in the Modulus 100;and tensile strength at break. The effects of all three factors were observed only in the case of the elongation at break. The morphology of the fracture surfaces of vulcanizates provided very good compatibility between lignosulfonate and rubber matrix.
Keywords: Lignosufonate; Multicomponent filler; Rubber Blends; Starch